Report
1941-11 038-0024-009 11 Nottingham. The Hon. Secretary in this area takes excellent care of the 16 children in the district, and has made special efforts to keep them together, by arranging meetings which give them an opportunity to talk in their mother tongue. Plymouth, till recently, ran a home for 12 children but had to close down hurriedly during the recent aerial bombardment of the city, and many debts were incurred in connection with this. They still care for five children, now living with Foster Parents. Pounsley Farm, Blackboys, Sussex. This was a most successful colony of 22 children, and although no longer functioning as a hostel now, still have three boys; two are being trained in agriculture and farm work, the remaining younger boy attending a secondary school in Kent. Reigate, in Surrey, is also a centre of sympathetic interest for adult Spaniards, and the five Basque children who still remain. They are fortunate in being in the closest contact with the Hon. Secretary of Reigate Committee, one of our oldest friends. Teeside and Tyneside. A small active group who still keep in close touch with the five children remaining in the area. Worthing. Although discontinued as an active Committee, keeps in touch with the Central Committee, through its former Hon. Secretary. At one time it ran one of the Committee's most successful girls' homes. Woolwich, S.E. London, maintained by local support an excellent colony for 18 Basques; they still care for one older boy training as a draughtsman, and a family of three waiting to join their parents in Mexico. Yorkshire still care for and billet 17 children, and although it is no longer possible to collect large sums of money, as they have in the past, raise sufficient to cover the expenses in connection with this work. For some time it has been the Committee's policy to find individual Foster Parents for the children unlikely to be repatriated, where they could live and attend a local school. Very careful inquiries were first made, and they have since been visited at regular intervals either by the Secretary of the Basque Children's Committee 292/946/38/24(IX)